Developing Canva-Based TBLT Learning Media Integrating Local Culture Patu Cambe to Enhance Students’ Speaking Skills - Pratiwi, Ayu; Masita, Masita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research focuses on developing Canva-based Task-Based Language Teaching (TBLT) media, enriched with the local Patu Cambe culture, to enhance students' English speaking skills. The study addresses the problem of low speaking proficiency among students, characterized by difficulties in pronunciation, vocabulary, self-confidence, and a lack of engaging learning media. The proposed solution integrates TBLT with visual media like Canva and local cultural content to foster interactive and creative learning, thereby increasing emotional involvement and cultural identity. The research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The target participants are students from the English Language Education Study Program at STKIP Al Amin Dompu. The study demonstrates that combining task-based learning approaches with digital tools like Canva creates engaging and interactive learning environments that foster greater motivation, confidence, and fluency among students. The integration of culturally relevant content, such as Patu Cambe, serves as a mediational tool that not only facilitates language development but also strengthens students' cultural identity, making learning more meaningful and contextually relevant. The quantitative results support this, showing a statistically significant increase in posttest scores from 78.47 to 86.06 (p < 0.001), with a large effect size, indicating the effectiveness of this approach in improving speaking proficiency